Political Islam in Context of Inter-Civilizational Conflicts - Y. B. Shipitsyn (Научный диалог, 2017)
The phenomenon of Islamism is considered in the context of global civilizational processes. Features of political Islam are studied in the context of the conflict between technogeneous and anthropogenic civilizations. It is alleged that such a conflict determines the level of demand of Islamist movements in different historical periods, the basis of the understanding these processes, their prediction and the development of possible tools to correct them. The author notes that the emergence and development of Islam as most of the world’s religious movements took place in conditions of political bruises and the search for new ways of development meeting the current challenges. It is shown that this circumstance largely determined both the internal structure of these movements and the principles of their interaction with the external environment. It is proved that the Islamic systems confront the modern (primarily Western) society by seeing the basis of statehood in the spiritual (non-material) traditions. The author believes that political Islam is struggling not just with some isolated phenomena in society, but, in principle, with the structure and values of the modern Western (Anglo-American, Atlantic) civilization.